Experimental Study on the Effect of Nano Additives γAl2O3 and Equivalence Ratio to Bunsen Flame Characteristic of Biodiesel from Nyamplung (Calophyllum Inophyllum) - Setyo Pambudi; Nasrul Ilminnafik; Salahuddin Junus; Muh Nurkoyim Kustanto (Automotive Laboratory of Universitas Muhammadiyah Magelang in collaboration with Association of Indonesian Vocational Educators (AIVE), 2021)
Nano γAl2O3 has been one of the nanometal oxides that has improved the characteristics of biodiesel. The effect of γAl2O3 nanoparticles addition on premixed flame combustion is investigated with an experiment on the laminar flame speed of Calophyllum inophyllum methyl ester 30% and 70% petrodiesel mixtures, at atmospheric pressure and preheated temperature T = 473K. The γAl2O3 nanoparticles added to CIME30 biodiesel were 0ppm, 100ppm, 200ppm, and 300ppm. Experiments were carried out on a bunsen burner. The equivalent ratio of the mixture between ϕ = 0.67 to 1.17. Experiments revealed that the addition of nanoparticles to CIME30 biodiesel expands the flammability limit and increases the laminar flame speed. CIME30 without nanoparticles, flame stable between ϕ = 0,76 -1,17. CIME30 with nanoparticles, flame stable between ϕ = 0,67 -1,17. Combustion of CIME30 required a lot of air. The highest laminar flame speed occurred at the equivalent ratio ϕ = 0.83. The highest laminar flame speed of CIME30 0, 100, 200, and 300 ppm were 30.77, 34.50, 35.90, 38.45 cm/s respectively. The higher the nano γAl2O3 concentration the higher the laminar flame speed. This occurs due to the catalytic effect of γAl2O3 on biodiesel and its mixtures.